A preliminary study evaluating self-reported effects of cannabis and cannabinoids on neuropathic pain and pain medication use in people with spinal cord injury - Kinnunen, Kristiina; Robayo, Linda E.; Cherup, Nicholas P.; Frank, Scott I.; Widerström-Noga, Eva (Frontiers in Pain Research, 2023)
Approximately 60% of individuals with a spinal cord injury (SCI) experience neuropathic pain, which often persists despite the use of various pharmacological treatments. Increasingly, the potential analgesic effects of cannabis and cannabinoid products have been studied; however, little research has been conducted among those with SCI-related neuropathic pain. Therefore, the primary objective of the study was to investigate the perceived effects of cannabis and cannabinoid use on neuropathic pain among those who were currently or had previously used these approaches. Additionally, the study aimed to determine if common pain medications are being substituted by cannabis and cannabinoids. Participants (N = 342) were recruited from existing opt-in listserv sources within the United States. Of those, 227 met the inclusion criteria and were enrolled in the study. The participants took part in an anonymous online survey regarding past and current use of cannabis and their perceived effects on neuropathic pain, including the use of pain medication. Those in the sample reported average neuropathic pain intensity scores over the past week of 6.8 ± 2.1 (0 to 10 scale), reflecting a high moderate to severe level of pain. Additionally, 87.9% noted that cannabis reduced their neuropathic pain intensity by more than 30%, and 92.3% reported that cannabis helped them to better deal with their neuropathic pain symptoms. Most participants (83.3%) also reported substituting their pain medications with cannabis, with the most substituted medication categories being opioids (47.0%), gabapentinoids (42.8%) and over-the-counter pain medications (42.2%). These preliminary results suggest that cannabis and cannabinoids may be effective in reducing neuropathic pain among those with SCI and may help to limit the need for certain pain medications.